Reduction of catheter-associated bloodstream infections through procedures in newborn babies admitted in a university hospital intensive care unit in Brazil - Resende,Daiane Silva (2011)
INTRODUCTION: Catheter-associated bloodstream infection (CA-BSI) is the most common nosocomial infection in neonatal intensive care units. There is evidence that care bundles to reduce CA-BSI are effective in the adult literature. The aim of this study was to reduce CA-BSI in a Brazilian neonatal intensive care unit by means of a care bundle including few strategies or procedures of prevention and control of these infections. METHODS: An intervention designed to reduce CA-BSI with five evidence-based procedures was conducted. RESULTS: A total of sixty-seven (26.7%) CA-BSIs were observed. There were 46 (32%) episodes of culture-proven sepsis in group preintervention (24.1 per 1,000 catheter days [CVC days]). Neonates in the group after implementation of the intervention had 21 (19.6%) episodes of CA-BSI (14.9 per 1,000 CVC days). The incidence of CA-BSI decreased significantly after the intervention from the group preintervention and postintervention (32% to 19.6%, 24.1 per 1,000 CVC days to 14.9 per 1,000 CVC days, p=0.04). In the multiple logistic regression analysis, the use of more than 3 antibiotics and length of stay >8 days were independent risk factors for BSI. CONCLUSIONS: A stepwise introduction of evidence-based intervention and intensive and continuous education of all healthcare workers are effective in reducing CA-BSI.